A CTP Synthase Undergoing Stage-Specific Spatial Expression Is Essential for the Survival of the Intracellular Parasite Toxoplasma gondii - Narvaez-Ortiz, Heidy Y.; Lopez, Andrea J.; Gupta, Nishith; Zimmermann, Barbara H. (Frontiers in Cellular and Infection Microbiology, 2018)
Cytidine triphosphate synthase catalyzes the synthesis of cytidine 5′-triphosphate (CTP) from uridine 5′-triphosphate (UTP), the final step in the production of cytidine nucleotides. CTP synthases also form filamentous structures of different morphologies known as cytoophidia, whose functions in most organisms are unknown. Here, we identified and characterized a novel CTP synthase (TgCTPS) from Toxoplasma gondii. We show that TgCTPS is capable of substituting for its counterparts in the otherwise lethal double mutant (ura7Δ ura8Δ) of Saccharomyces cerevisiae. Equally, recombinant TgCTPS purified from Escherichia coli encodes for a functional protein in enzyme assays. The epitope-tagged TgCTPS under the control of its endogenous promoter displays a punctate cytosolic distribution, which undergoes spatial reorganization to form foci or filament-like structures when the parasite switches from a nutrient-replete (intracellular) to a nutrient-scarce (extracellular) condition. An analogous phenotype is observed upon nutrient stress or after treatment with a glutamine analog, 6-diazo-5-oxo-L-norleucine (DON). The exposure of parasites to DON disrupts the lytic cycle, and the TgCTPS is refractory to a genetic deletion, suggesting an essential requirement of this enzyme for T. gondii. Not least, this study, together with previous studies, supports that CTP synthase can serve as a potent drug target, because the parasite, unlike human host cells, cannot compensate for the lack of CTP synthase activity.